Pengaruh Digital Marketing dan Daya Tarik Wisata Terhadap Minat Berkunjung di Objek Wisata Kabupaten Pulau Morotai Provinsi Maluku Utara - Dwi Aprianto, Mohammad Andri (Idarotuna : Journal of Administrative Science, 2025)
The study sought to ascertain how digital marketing and tourist attractions affect visitor interest in Morotai Island Regency's tourist attractions in North Maluku Province.  A quantitative methodology was employed, utilizing primary data as the source.  The method of data collection involved using questionnaires that were distributed to visitors at 44 tourist sites in Morotai Island Regency, North Maluku Province.  The sample comprised 150 respondents.  Data analysis was conducted using multiple linear regression. According to the study's findings, visitor interest is considerably and beneficially influenced by digital marketing. Tourist attractions positively and significantly influence visitor interest. In Morotai Island Regency, North Maluku Province, both digital marketing and tourist attractions have a notable and beneficial impact on visitor interest in these attractions. This study concludes that digital marketing has the potential to generate public interest in visiting tourist attractions on Morotai Island, located in North Maluku Province.